HIV-positive demonstrate more salt sensitivity and nocturnal non-dipping blood pressure than HIV-negative individuals - Sepiso K. Masenga; Annet Kirabo; Benson M. Hamooya; Selestine Nzala; Geoffrey Kwenda; Douglas C. Heimburger; Wilbroad Mutale; John R. Koethe; Leta Pilic; Sody M. Munsaka (BMC, 2021)
Abstract Background High dietary salt and a lack of reduced blood pressure (BP) at night (non-dipping) are risk factors for the development of hypertension which may result in end-organ damage and death. The effect of high dietary salt on BP in black people of sub-Saharan Africa living with HIV is not well established. The goal of this study was to explore the associations between salt sensitivity and nocturnal blood pressure dipping according to HIV and hypertension status in a cohort of adult Zambian population. Methods We conducted an interventional study among 43 HIV-positive and 42 HIV-negative adults matched for age and sex. Study participants were instructed to consume a low (4 g) dietary salt intake for a week followed by high (9 g) dietary salt intake for a week. Salt resistance and salt sensitivity were defined by a mean arterial pressure difference of ≤5 mmHg and ≥ 8 mmHg, respectively, between the last day of low and high dietary salt intervention. Nocturnal dipping was defined as a 10-15% decrease in night-time blood pressure measured with an ambulatory blood pressure monitor. Results The median age was 40 years for both the HIV-positive and the HIV-negative group with 1:1 male to female ratio. HIV positive individuals with hypertension exhibited a higher BP sensitivity to salt (95%) and non-dipping BP (86%) prevalence compared with the HIV negative hypertensive (71 and 67%), HIV positive (10 and 24%) and HIV-negative normotensive (29 and 52%) groups, respectively (p < 0.05). Salt sensitivity was associated with non-dipping BP and hypertension in both the HIV-positive and HIV-negative groups even after adjustment in multivariate logistic regression (< 0.001). Conclusions The results of the present study suggest that high dietary salt intake raises blood pressure and worsens nocturnal BP dipping to a greater extent in hypertensive than normotensive individuals and that hypertensive individuals have higher dietary salt intake than their normotensive counterparts. Regarding HIV status, BP of HIV-positive hypertensive patients may be more sensitive to salt intake and demonstrate more non-dipping pattern compared to HIV-negative hypertensive group. However, further studies with a larger sample size are required to validate this.